2012
DOI: 10.1002/anie.201204116
|View full text |Cite
|
Sign up to set email alerts
|

Model and Mechanism: N‐Hydroxylation of Primary Aromatic Amines by Cytochrome P450

Abstract: Only one path applies: to date, five different mechanisms have been suggested for the P450-catalyzed N-hydroxylation of primary aromatic amines. Computational analysis employing density functional theory demonstrates that only the H-atom-transfer pathway, that is H abstraction from an amine N followed by a radical rebound step, on a low-spin route can contribute to the aromatic hydroxylamine formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
80
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 70 publications
(91 citation statements)
references
References 44 publications
8
80
3
Order By: Relevance
“…This is different from the reaction between methylamine and P450, for which it was concluded that nitrogen oxidation should be more favorable 16b. The mechanism involving preferred hydrogen abstraction is similar to the mechanism proposed for the reaction of aniline 25b…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…This is different from the reaction between methylamine and P450, for which it was concluded that nitrogen oxidation should be more favorable 16b. The mechanism involving preferred hydrogen abstraction is similar to the mechanism proposed for the reaction of aniline 25b…”
Section: Resultsmentioning
confidence: 76%
“…used DFT to investigate the reaction of methylamine that finally gives a nitroso‐type MI and concluded that the nitrogen‐oxidation mechanism is more favorable than the hydrogen‐abstraction mechanism 16b. In the reaction of aniline, however, Ji and Schüürmann showed that hydrogen abstraction is preferred over nitrogen oxidation 25b. In view of these two mechanisms that may be involved in the reactions of primary amines, it is of interest to examine, in addition to the hydrogen‐abstraction mechanism shown in Scheme , the nitrogen‐oxidation mechanism for hydrazine reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous computational models have been developed to investigate as many as five different potential mechanisms for N- oxidation of aromatic amines. 8183 While a consensus remains to be reached, computational analyses support two mechanisms: a hydrogen atom transfer (HAT) mechanism (Path A, Scheme 3) and a proton transfer (PT) mechanism (Path B, Scheme 3). …”
Section: N–o Bond Forming Enzymesmentioning
confidence: 99%
“…Computational modeling by Schüürmann et al recently suggested that this pathway is the most feasible route for ArNH 2 hydroxylation. 83 Furthermore, radical-based mechanisms for N–O bond formation have been previously proposed, but not supported with mechanistic studies, for nitroso formation by the di-copper enzyme NspF in ferroverdin biosynthesis (Section 2.5.1) 97 and nitro formation by the di-iron enzyme CmlI in chloramphenicol biosynthesis (Section 2.6.1.1). 98 For NOS, extensive electron paramagnetic resonance (EPR) and electron nuclear double resonance (ENDOR) studies have provided evidence that N–O bond formation proceeds through 24 (Section 2.4.1).…”
Section: N–o Bond Forming Enzymesmentioning
confidence: 99%
“…Interestingly, a similar pattern has been observed recently for the HAT pathway of the N-hydroxylation of primary aromatic amines, featuring a P450-catalyzed one-step reaction to the rebounded N-hydroxylamine product only in the LS state. 53 By contrast, the respective HS route proceeded through an intermediate that could convert into the rebound product only through a significant and ratedetermining reaction barrier. Note further that regarding the P450-catalyzed α-CH hydroxylation of nitrosamines, which is also subject to a HAT mechanism as well as most alkanes, for both the HS and LS state there have been found intermediates, followed by a reaction barrier only in the HS route (which, however, was lower than the preceding H-abstraction barrier).…”
Section: Chemical Research In Toxicologymentioning
confidence: 99%